An Assessment of Preschool Education Options for Rural and Small Village Areas - Walter E. Sawyers; Jean C. Sawyer (Journal of Research in Rural Education, 1982)
The purpose of the study was to determine the effects of four preschool experiences on seven readiness skill areas. The preschool experiences included no treatment,a home based program,a formal preschool program,and a combination of the latter two programs. The seven dependent variable readiness skills were verbal memory, fine motor skill (draw a design), numerical memory,conceptual grouping, gross motor skill (leg coordination),a composite of the five areas and receptive language. Analyses of. variance and Scheffe procedures were used to analyze data. The group receiving the combination program differed positively and significantly from the other groups in both numerical memory and conceptual grouping. A similar finding was observed in conceptual grouping for the home based program group.It was concludedthata cooperative home/school bond is important for improving preschool readiness skills.It was further concluded that a home basedprogramcan provide important experiences related to child development in geographical areas where formal preschool programs are not available.